Juizados Especiais Criminias da Comarca da Capital do Estado do RIo de janeiro: Desafios organizacionais - Monteiro, Paulo Maurício Pinheiro (2002)
The Judicial Authority has more and more prominence for the principal place on the public discussion. His role performed as political institution and agency in charged of the jurisdiction installment has been object of discussion. Frequently diagnostics are made about a crisis that include the Judicial System. At the same way are made diverse changes, searching transform from formalities until the ritual of fill a job of Judge. We¿re certainly, by this point of view, far from the period that the judicial questions were corresponded to jurisconsult. The discussion has increased, calling to order not only jurisconsult but also members of Congress, press and of the civil organisms. Thus international organisms, despite their economic issues, entered at the discussion being watchful to the emergency reforms to be taken by the Judicial Authority. However, although the changes end the relative agreement of the emerging crisis, the Judicial System continue to be unknown. Still now with the beginning of the Juizados Especiais Criminais, the organizational form originated in 1995. The main core of the discussion about Juizados Especiais Criminais is centralized in isolated cases instead of a global analysis, resulting of the join between data and observations about historic series. The final object of this dissertation is centered on the analysis of the activities of the organizational variables of the Juizados Especiais Criminais da Comarca da Capital do Estado do Rio de Janeiro in its first years of functioning.